Enhancing Quality Education: The Synergy of Culturally Responsive Teaching and Student Interest on Learning Outcomes in Elementary Schools - Murniyenti; Jasrial; Darmansyah; Fetri Yeni J (Postgraduate, University of Mataram, 2026)
This study examines the impact of Culturally Responsive Teaching (CRT) and learning interest on the mathematics learning outcomes of fifth-grade students, focusing on the perimeter and area of plane figures. Aimed at addressing passive engagement in conventional methods, this quasi-experimental research employed a 2x2 factorial design with 42 students. Data were collected via learning interest questionnaires and mathematics tests, then analyzed using Independent Sample T-Tests and Two-Way ANOVA. The results demonstrate that CRT significantly improves overall mathematics learning outcomes (p = 0.000). Specifically, CRT has a significant positive effect on students with high learning interest (p = 0.008) with a mean difference of 13.45 points, and on those with low learning interest (p = 0.000) with a mean difference of 12.15 points. Furthermore, a significant interaction exists between the teaching approach and learning interest (p = 0.043). These findings suggest that CRT effectively enhances outcomes across different interest levels by integrating local culture, such as the Jam Gadang, into the Merdeka Curriculum. This approach promotes inclusive, contextual, and meaningful learning in elementary education.